2011
DOI: 10.1055/s-0031-1296557
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Ambroxol Lozenges in the Treatment of Acute Uncomplicated Sore Throat

Abstract: Sore throat is the hallmark of acute pharyngitis. Although usually caused by viral infections, it is frequently treated with antibiotics. Such inappropriate use of antibiotics might best be challenged by offering efficacious and safe symptomatic pain relief instead. However, there is need for robust evidence to support such alternatives. Presently, the evidence from randomised, placebo-controlled, double-blind clinical trials (RCT) with the local anaesthetic ambroxol (CAS 23828-92-4) in the treatment of sore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 61 publications
(53 reference statements)
0
16
0
Order By: Relevance
“…Randomized, placebo-controlled short-term (up to 2 weeks of treatment) studies showed efficacy against endpoints such as ease of expectoration, phlegm loosening, sputum volume and sputum viscosity [1113]. Moreover, more recent studies have demonstrated the efficacy of ambroxol lozenges in the treatment of sore throat [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Randomized, placebo-controlled short-term (up to 2 weeks of treatment) studies showed efficacy against endpoints such as ease of expectoration, phlegm loosening, sputum volume and sputum viscosity [1113]. Moreover, more recent studies have demonstrated the efficacy of ambroxol lozenges in the treatment of sore throat [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Three RCTs were published twice [14,16]. One publication summarized all previously published trials providing additionally data from two so far unpublished trials in a so called EBM-based clinical documentation [15]. We identified additionally two unpublished registered and completed RCTs in the study registry ClinicalTrial.gov .These did not provide enough data to be included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…All trials compared 20 mg ambroxol with placebo. There was a dose finding study comparing additionally 5 and 10 mg ambroxol [15] with placebo and two studies had a treatment arm with 30 mg ambroxol [14,16]. One study included a treatment arm with the local anaesthetic benzocaine, but outcomes were not reported [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ambroxol is a well-tolerated agent commonly used for the treatment of respiratory disorders via its secretolytic, secretomotor and local anaesthetic effects in cases of pharyngalgia [108]. Regarding mechanisms of action, ambroxol is a potent voltage-dependent sodium channel blocker, blocking these channels approximately 40 times more strongly than lidocaine [109].…”
Section: Introductionmentioning
confidence: 99%